An Analysis Of Hyperbole In Album “The Chainsmoker" - I Wayan Juniartha; Ni Nyoman Deni Ariyaningsih; Riky Astina (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2021)
This article discusses the hyperbole figure used in the lyrics of Chainsmokers songs. The author assumes that the hyperbole figurative language in the song lyrics is used to attract song lovers to be interested in buying original, not pirated, CD tapes. The article, entitled "Hyperbola language used in chainsmokers' songs, aims to identify the types and find the meaning of the hyperbola language in the song. To analyze the data, the main theory used in this article is the figurative language theory proposed by Knickerbocker and Reninger 1963, the theory of meaning proposed by Leech 1981 and some of another supporting theory. This article uses qualitative methods to provide a clear picture of the problems identified. Descriptive study in textual analysis is applied to describe the types and meanings of hyperbolic figures in the song lyric. The data is taken from several editions of the song released in 2017-2020.